The postcranial anatomy of Endothiodon bathystoma (Anomodontia, Therapsida). (3rd July 2021) - Maharaj, Iyra E. M.; Chinsamy, Anusuya; Smith, Roger M. H.
ABSTRACT: Dicynodonts were herbivorous non-mammalian synapsids that were relatively abundant on the landmass of Pangea from the Mid Permian to Late Triassic. The dicynodont genus Endothiodon is well known from late Permian strata of the Karoo Basin of South Africa. It is characterised by replacement waves of internal tooth rows on the premaxilla and dentary; longitudinal ridges from the premaxilla to the pineal crest; and a pineal foramen on a prominent boss. Endothiodon is well-represented by cranial and postcranial material in various South African museum collections. Recently, an almost complete skeleton of Endothiodon (SAM-PK-K011271) was recovered from the uppermost Pristerognathus Assemblage Zone of the Karoo Supergroup. It comprises the skull and most postcranial elements preserved in articulation. The present study identifies SAM-PK-K011271 as E. bathystoma and we show that it is the second largest E. bathystoma specimen known to date. Furthermore, the well-preserved skeletal remains enable us to present the first comprehensive description of its postcranial anatomy. Abbreviations Institutional abbreviations: AM: Albany Museum, Grahamstown, South Africa; CGS: Council for Geosciences, Pretoria, South Africa; ESI: Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg, South Africa; ISI: Indian Statistical Institute, Kolkata, India; SAM: Iziko South African Museum, Cape Town, South Africa.Anatomical abbreviations: ang, angular; art, articular; ast, astragalus; br, M. brachialis; c, centrale; ca, calcaneum; cb, M. coracobrachialis; cbl, M. coracobrachialis longus; Cd, caudal vertebra; d, dentary; del, M. deltoideus; ent, entepidcondyle; ent f, entepicondylar foramen; f, frontal; fti, M. femorotibialis; H, height; ife, M. iliofemoralis; ifi, M. iliofibularis; it, M. incisura tibialis fossa; iti, M. iliotibialis; il, ilium; is, ischium; j, jugal; l, lacrimal; M., metacarpal; mf, mandibular fenestra; Mt., metatarsal; n, nasal; nc, neural canal; ns, neural spine; ol, olecranon; P., phalanx; pb, pineal boss; pec, M. pectoralis; pifi, M. puboischiofemoralis internus; piti, M. puboischiotibialis; pm, premaxilla; po, postorbital; poz, postzygapophyses; prz, prezygapophyses; pp, preparietal; psf, postspinal fossa; pu, pubis; q, quadrate; r con, radial condyle; ref. l, reflected lamina; S, sacral vertebra; sas, M. serratus anterior superficialis; sc, M. subcoracoideus; scs, M. subcoracoscapularis; sha, M. scapulohumeralis anterior; SL, skull length; spc, M. supracoracoideus; sq, squamosal; sup, supinator; SW, skull width; tha, M. triceps humeralis anterior; thm, M. triceps humeralis medialis; tp, transverse process; tri, M. triceps; W, width.